Identification of the TPC2 interactome reveals TSPAN10 and OCA7 as key players in the biogenesis of melanosomes - Beyers, Wyatt, author; Di Pietro, Santiago, advisor; Amberg, Gregory, committee member; Santangelo, Thomas, committee member; Yao, Tingting, committee member (Colorado State University. Libraries, 2023)
Many specialized cell types gain their function through the generation of specialized organelles that make or store cell-specific biomolecules. A group of specialized organelles are called Lysosome Related Organelles (LROs) because they are derived from Golgi and endolysosomal compartments and their biogenesis depends on trafficking pathways and machinery shared with lysosomes, many have protein contents partially overlapping with lysosomes, and typically have low pH during stages of their maturation. One well-studied model LRO is the melanosome, the organelle in melanocytes and retinal pigment epithelial cells responsible for melanin pigment production in the eyes, hair, and skin, and defects in melanosome function lead to pigmentation diseases such as oculocutaneous albinism. Melanosome biogenesis is a complex process requiring ubiquitous membrane trafficking machinery to be repurposed for the differentiation of melanosomes from other endosomal compartments and specific delivery of melanosome synthesizing enzymes, Tyrosinase and Tyrosinase Related Proteins 1 and 2. Furthermore, correct melanosome maturation requires remodeling of the melanosome membrane, recycling of membrane trafficking machinery, generation of intraluminal amyloid fibrils with the correct structure for melanin packaging, tight pH control, as well as coordinated influx of copper, zinc, tyrosine, and cysteine for melanin synthesis. These processes require the temporospatial coordination of at least 100 known proteins, and probably dozens more remain undiscovered. In this dissertation, I present the discovery of new proteins involved in the biogenesis of melanosomes. Proximity biotinylation by promiscuous biotin ligase enzymes followed by biotin pulldown and mass spectrometry has emerged as a powerful technique for the identification of protein-protein interactions, protein complex determination, and identification of organelle membrane proteomes. I utilized the melanosome localized cation channel, TPC2, genetically fused with the BioID2 biotin ligase, to identify proteins in proximity to TPC2 at the cytosolic surface of melanosome membranes of MNT1 melanoma cells. Through mass spectrometry analysis of biotinylated proteins enriched through Streptactin pulldown, a TPC2 proximity interactome was identified comprising over 200 proteins. Subsequent fluorescence confocal microscopy analysis confirmed several proteins, including PLD1, SV2A, TSPAN10, and OCA7/C10orf11/LRMDA all colocalize highly with TPC2-EGFP, confirming they are new melanosome proteins. In follow-up functional studies, TSPAN10 and OCA7 were confirmed to be involved in pigmentation, with severe melanin depletion in TSPAN10 or OCA7 knockout MNT1 cells. TSPAN10 and OCA7 both influence the processing of the PMEL protein, which is required for correct melanosome ultrastructure and for melanin packaging. Further investigation of TSPAN10 revealed it functions with the pigmentation associated metalloproteinase, ADAM10, and is required for ADAM10 expression and localization to endosomal compartments. On the other hand, OCA7 was found to work with the melanosome localized Rab proteins, Rab32 and Rab38, and regulates the pH of melanosomes. Thus, the newly defined TPC2 interactome in melanocytes was proven as a valuable dataset that robustly identifies new melanosome proteins. Chapter 1 of this dissertation provides a broad overview of membrane trafficking pathways, as well as a synopsis of the specific proteins and pathways involved in melanosome biogenesis and homeostasis. Chapter 2 investigates the TPC2 interactome in MNT1 cells, and it characterizes TSPAN10 as a new player in melanosome biogenesis. Finally, Chapter 3 provides a characterization of the OCA7 protein associated with oculocutaneous albinism type 7 and investigates OCA7 function using a newly generated OCA7 knockout cell model.
Keywords: membrane trafficking; pigmentation; TSPAN10; OCA7; melanosome; TPC2